Aglomeração ItabunaI - lhéus : cidade, região e rede urbana - Trindade, Gilmar Alves (2011)
This study examines the genesis, development and current configuration of the urban network in the territorial agglomeration of Itabuna - Ilhéus (BA). Its region of influence went through major transformations over the last two decades (1990 2010) due to economic crisis, linked, among other reasons to a decline of cocoa production, which is the basis of the regional economy. These transformations altered rhythm, intensity, content and volume of the spatial interactions between regional centers and small cities. Cocoa flows, which are historically related to production, circulation and marketing were reduced while new flows emerged in association to other potentialized productive activities in regional centers and even some small cities. These socio-spatial changes altered form and content of the regional urban network, but that does not mean that hierarchical relationships have disappeared, because, as the most modern fixed geographic continued to be placed in Itabuna and Ilhéus, small cities remained dependent on them even relying on less hierarchical relationships than in recent past. Methodologically, it was chosen to use a routing theoretical-conceptual based on Santos (1994, 1996a, 1996b, 1999) through interpretation of space as a system of objects and actions in which fixed and flows, verticality and horizontality coexist integrating society and territory as dialectical pairs that compose the totality of the geographical space in which the urban network is the main connecting element. The implements used for data collection relied on direct and indirect observation; random application of questionnaires to entrepreneurs and traders in seventeen selected cities; application of structured interviews to social segments selected in Itabuna and Ilhéus; application of informal interviews to different social segments in Itabuna, Ilhéus and also in the seventeen selected cities; online surveys in selected sites; data collection in institutions as well as public and private selected companies and cartographic treatment. Among conclusions, the study highlighted that despite instant connections made possible by technical and informational means, it is still not possible to abandon the idea of urban hierarchy, after all, the responsible fixed for the densification of flows in the network continues to be selectively installed in the territory of Itabuna and Ilhéus; and these two cities combine in condition of complementarity, interactions in a scale that is not only regional, but baiana, brazilian and worldwide as well, playing the role of regional capital in the brazilian urban network only if considered on the spatial form of an urban agglomeration.